Pressure-Regulated Gene Expression and Enzymatic Activity of the Two Periplasmic Nitrate Reductases in the Deep-Sea Bacterium Shewanella piezotolerans WP3 - Li, Xue-Gong; Zhang, Wei-Jia; Xiao, Xiang; Jian, Hua-Hua; Jiang, Ting; Tang, Hong-Zhi; Qi, Xiao-Qing; Wu, Long-Fei (Frontiers in Microbiology, 2018)
Shewanella species are widely distributed in marine environments, from the shallow coasts to the deepest sea bottom. Most Shewanella species possess two isoforms of periplasmic nitrate reductases (NAP-α and NAP-β) and are able to generate energy through nitrate reduction. However, the contributions of the two NAP systems to bacterial deep-sea adaptation remain unclear. In this study, we found that the deep-sea denitrifier S. piezotolerans WP3 was capable of performing nitrate respiration under high hydrostatic pressure (HHP) conditions. In the wild-type strain, NAP-β played a dominant role and was induced by both the substrate and an elevated pressure, whereas NAP-α was constitutively expressed at a relatively lower level. Genetic studies showed that each NAP system alone was sufficient to fully sustain nitrate-dependent growth and that both NAP systems exhibited substrate and pressure inducible expression patterns when the other set was absent. Biochemical assays further demonstrated that NAP-α had a higher tolerance to elevated pressure. Collectively, we report for the first time the distinct properties and contributions of the two NAP systems to nitrate reduction under different pressure conditions. The results will shed light on the mechanisms of bacterial HHP adaptation and nitrogen cycling in the deep-sea environment.